Detection and activity of 11 beta hydroxylase (CYP11B1) in the bovine ovary - Amweg, Ayelen Noelia (2017)
Glucocorticoids (GCs) such as cortisol and corticosterone are important steroid hormones with different functions in intermediate metabolism, development, cell differentiation, immune response and reproduction. In response to physiological and immunological stress, adrenocorticotropic hormone (AC TH) acts on the adrenal gland by stimulating the synthesis and secretion of GCs. However, there is increasing evidence that GCs may also be synthesized by extra-adrenal tissues. Here, we examined the gene and protein expression of the enzyme 11β-hydroxylase P450c11 (CYP11B1), involved in the conversion of 11-deoxycortisol to cortisol, in the different components of the bovine ovary and determined the functionality of CYP11B1 in vitro. CYP11B1 mRNA was expressed in granulosa and theca cells in small, medium and large antral ovarian follicles, and CYP11B1 protein was expressed in medium and large antral follicles. After stimulation by AC TH, we observed an increased secretion of cortisol by the wall of large antral follicles. We also observed a concentration-dependent decrease in the concentration of cortisol in response to metyrapone, an inhibitor of CYP11B1. This decrease was significant at 10-5 μM metyrapone. In conclusion, this study demonstrated for the first time the presence of CYP11B1 in the bovine ovary. This confirms that there could be a local synthesis of GCs in the bovine ovary and therefore a potential endocrine responder to stress through these hormones.